Educating for citizen leadership: exploring the University of Cape Town’s global citizenship programme - Joseph, Loren (Department of Psychology, 2020)
This dissertation explores the University of Cape Town’s Global Citizenship (GC) Programme as a site for teaching citizen leadership. We live in times that are marked by complexity, uncertainty, and a plethora of global challenges, many of which have resulted in injustices in people’s lived experiences. Increasingly ordinary citizens are calling for new ways of leading change which combats social injustices. This form of leadership values social justice, democracy, equity, shared agency, active and engaged citizenship – this is regarded as citizen leadership. Higher education institutions have a role to play in developing student leaders who are equipped with the capacities to confront uncertainty and thrive in a changing world. This study recruited student participants of the GC programme courses. In total, ten students participated in one of four focus group discussions which were guided by semi-structured interviews, and ninety students consented to have their reflective essays on the GC programme courses analysed. Using Interpretative Phenomenological Analysis, the participants’ experience of the programme, in the focus group discussions and reflective essays, was examined to determine how they understood citizenship, social justice and leadership in relation to the programme’s teachings. The findings revealed that most students regarded the programme as developing their capacities for active and engaged global citizenship. Most students did not view the programme as teaching leadership; however, based on the definition of citizen leadership, I argue that the programme is indeed a site for teaching this form of leadership. It is recommended that the programme staff make the connection between active and engaged citizenship, social justice, and leadership more explicit in their curricula and teaching. It is believed that this change to the programme will enable students to have a clearer understanding of themselves as leaders prepared for the world beyond university and enabled to bring purposeful change to the world.